MOTIVASI KONSUMEN MUSLIM DALAM MEMBELI MAKANAN DI RETORAN NON-MUSLIM - Dewi Rahayu (Al - Muamalat: Jurnal Hukum dan Ekonomi Syariah, 2016)
Nowadays people realize that daily food consumed affect health and knows the food is halal or not. To get the best food, consumer faced by choosing from moeslem’s or nonmoeslem’s restaurant. The reality we can found any moeslem consumer at nonmoeslem’s restaurant. Method that used in this research is descriptive quantitative. Collecting data technique are by questionaries, interview and documentation by likert scale. The overall research result of correlation cofficients counting obtain that first, 0.985 valued by hygiene factor. Second, 0.892 valued by price factor. Third, 0.632 valued by taste factor. Fourth, 0.368 valued by quality factor. Fifth, -0,666 valued by service factor. Sixth, -1,158 valued by promotion factor. From all owner nonmoeslem’s Restaurant that interviewed, we can conclude that Segar Restaurant use same kitchen for personal and business. Solo Muda Restaurant and Warkop 88 use different kitchen for personal an business. While Purnama Restaurant deny to interviewed by researcher. All interview’s result with MPU partner Kota Langsa, researcher conclude that verdict of consuming food at nonmoeslem’s restaurant is syubhat.